(untitled) (Vietnam Journal of Community Medicine, 2024)
Aim: Evaluating the role and effect of heral medicine, traditional medicine decotion and products on treat gout in Vietnam. Method: Scoping review. Results: Among 404 related article found, 8 articles that meet inclusion criteria were involved to this ressearch, including 2 clinical trials and 6 experimental trials. Acid uric decreasing effect was reported in all included articles. Pain decreasing and symptom improving effects were found in 2 clinical research. These effects were signigicantly reported. Conclution: These researches on the effect of traditional medicine on managing gout initially shows effectives outcomes. However, more high level researches should be implemented to confirm those above mentioned effects.